Risk Factors associated with defaulting from visceral leishmaniasis treatment: analysis under routine programme conditions in Bihar, India. Issue 8 (13th July 2017) - Kansal, S.; Chakravarty, J.; Kumar, A.; Malaviya, P.; Boelaert, M.; Hasker, E.; Ostyn, B.; Sundar, S.
Abstract: Objective: To assess the rate of default from treatment in the visceral leishmaniasis (VL) elimination programme and to identify risk factors and its underlying causes. Methods: Case–control study conducted between December 2009 and June 2012 in three primary health centres (PHCs) of Muzaffarpur district, India. Patients who defaulted from treatment from the PHCs were considered as 'cases' and those who completed their treatment as 'controls'. Two controls were included in the study for each case. Respondents' opinion and satisfaction with the services provided at the PHCs were also elicited. Logistic regression was performed to assess the contribution of sociodemographic variables on patient status, and a discriminant analysis was used (after decomposing the original data) to identify factors that can predict the patient status as defaulter or not, based on factor scores of the components as predictor variables. Results: During the study period, 16.3% (89/544) of patients defaulted; 87 cases and 188 controls were interviewed through a semistructured questionnaire. Women tended to be more at risk for default (OR, 1.6, 95% CI (0.9 ‐2.9). Treatment received was miltefosine in 55.6% and sodium stibogluconate (SSG) in 44.4%. Most (86%) defaulters completed their treatment at other healthcare facilities; 70% of them preferred non‐governmental institutions. Most cited reasons for default were seeking a second opinion for VL treatment and preferring to be treated in specialised VL centres. Discriminant analysis showed only one significant predictor: dissatisfaction with the medical care received in PHCs. Conclusion: Efforts are needed to enhance the quality of VL care at PHC level, which will be beneficial in increasing treatment completion rates.